1995
DOI: 10.1007/bf00711162
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of (TTAGGG)n telomeric sequences and ribosomal genes in Atlantic eels

Abstract: The distribution of (TTAGGG)n telomeric repeats was studied in chromosomes of two Atlantic eels, Anguilla anguilla and A. rostrata. We found that these sequences hybridize to all the telomeres but also to the entire nucleolar organizer region (NOR) localized in both species at the short arm of chromosome 8. This was considered to be due to the interspersion of telomeric sequences within the NOR ones. Whatever the significance of this interspersion may be, it seems to be limited to A. anguilla and A. rostrata s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 14 publications
6
54
1
1
Order By: Relevance
“…81 This accumulation could explain the heteromorphism observed in the 5S rDNA and 18S rDNA sites in tamoatás, as previously observed in other fish and mammals. [82][83][84] Association between 18S rDNA and Rex3 are observed in the present study and can be related to dispersion of ribosomal sites, as have previously been observed in other Amazonian fish species. 12,85 Thus, probably 5S rDNA sites were duplicated and dispersed in the genome, since TEs are able to remove and insert themselves at other sites in the genome and are often duplicated during this process.…”
Section: Discussionsupporting
confidence: 87%
“…81 This accumulation could explain the heteromorphism observed in the 5S rDNA and 18S rDNA sites in tamoatás, as previously observed in other fish and mammals. [82][83][84] Association between 18S rDNA and Rex3 are observed in the present study and can be related to dispersion of ribosomal sites, as have previously been observed in other Amazonian fish species. 12,85 Thus, probably 5S rDNA sites were duplicated and dispersed in the genome, since TEs are able to remove and insert themselves at other sites in the genome and are often duplicated during this process.…”
Section: Discussionsupporting
confidence: 87%
“…In the at-lantic eels, Anguilla anguilla and A. rostrata (SALVADORI et al 1995) has been observed the presence of telomeric repeats interspersed within rDNA arrays and it has been hypothesised that such sequences could act as hotspot of recombination (ASHLEY and WARD 1993;SALVADORI et al 1995).…”
Section: Resultsmentioning
confidence: 99%
“…However, the visualization of 5S rDNA sites requires more specific techniques, such as fluorescence in situ hybridization (FISH). The fluorochromes that preferentially stain GCrich regions, such as mithramycin and chromomcyin A 3 (CMA 3 ), have also been widely used in chromosome preparations of fish to demonstrate the location of NORs, because according to Salvadori et al (1995), these regions are associated with DNA families rich in GC bases. More recently, FISH with rDNA probes has been utilized with precision to determine the exact location and number of ribosomal cístrons.…”
Section: Introductionmentioning
confidence: 99%